Psychotherapy and spirituality : integrating the spiritual dimension into therapeutic practice - Schreurs, A. (Agneta) (Jessica Kingsley Publishers, 2002)
Schreurs presents a range of therapeutic situations, analogies and case-studies in which spiritual concerns may arise, and explores them from spiritual and psychological perspectives, showing how they connect and differ. This engaging book is essential reading for all therapists who feel out of their depth when patients raise spiritual concerns.